2577. Periodontal Disease and the Oral Microbiome in Alcohol-Dependent Individuals - Meeks, Brianna K (Open Forum Infect Dis, 2019)
BACKGROUND: Periodontal disease results from a polymicrobial infection composed of pathogenic bacteria that colonize the oral cavity, resulting in loss of periodontal attachment and alveolar bone. Periodontitis can increase the risk or exacerbate other comorbidities. Alcohol use increases the risk of periodontitis, but there is little knowledge about periodontitis among people who misuse alcohol. METHODS: As part of a larger oral and gut microbiome study, this analysis examines the oral microbiome in the occurrence and severity of periodontitis among alcohol-dependent (AD) subjects undergoing a 28-day inpatient alcohol treatment program. Tongue brushings were collected from 22 subjects within the first week of admission, and 16S rDNA sequencing was performed. All subjects had a dental examination during the inpatient stay. This analysis divided periodontal disease status into three major groups–no disease, mild or moderate disease, and severe disease. One-way ANOVA was used to compare microbial genera across the 3 groups. RESULTS: Nineteen (86%) of the subjects had periodontitis: 16 had mild or moderate disease, and 3 had severe disease. Statistically different microbial genera in at least one of the three groups (P ≤ 0.05 corresponding to FDR ≤ 0.25) that had a relative abundance of at least 0.5% include: Bifidobacterium, Lactobacillus, Parvimonas, Peptostreptococcus, Porphyromonas, and Treponema. Surprisingly, the subjects with no periodontitis had increased abundances of genera that are often pathogens, Porphyromonas and Peptostreptococcus. Subjects with severe periodontitis had increased abundances of known pathogens Treponema and Parvimonas, as well as Lactobacillus, which has been associated with dental caries. CONCLUSION: We observed that periodontitis accompanies chronic AD, given that 86% of our subjects had the disease. While some microbiome differences for individuals with and without periodontitis were not consistent with the existing literature, this may have many explanations. Future studies should consider how chronic AD could change the microbial ecology of the mouth and lead to further infection as well as utilizing multiple oral sites and a larger sample size to better understand the relationship between AD and periodontal disease. Intramural funds from NIH DISCLOSURES: All authors: No reported disclosures.